Torta de amendoim na suplementação de vacas em lactação a pasto - Cerutti, Weiler Giacomazza (2013)
This paper aims to evaluate the daily milk production (DMP) and the composition and profile of fatty acidsin milk and the economy of concentrated supplement, as well as the income, the sensory characteristics and fatty acid profile of MinasFrescal cheese from cows on pasture receiving supplement containing peanut pie. We used eight lactating Holstein x Gir crossbred cows distributed in two 4x4 Latin square designs (four animals x four treatments x four periods). The experimental treatments consisted of four supplements containing the levels: 0; 33; 66; and 100% peanut pie (PP) in the dry matter of concentrate to replace soy bran (SB). There was no difference (P>0.05) for DMP and for contents of fat, protein, lactose, total solids, nonfat dry, urea N, and for the fat/protein between treatments. The levels of fatty acids C8:0; C10:0; C11:0; C12:0; and C18:2c9t11 reduced (P<0.05) with the increasing participation of PP in place of SB. For the other levels of fatty acids, there was no difference (P>0.05) among treatments. There was a reduction of R$70.00 per ton in the cost of the supplement, with 100% replacement. The yield of Minas Frescal cheese and their fat contents were similar (P>0.05) among treatments. However, when comparing the cheese subjected or not to thermal processing, we observed that it took an average of 6.7 and 5.9 liters of milk to process one kilogram of cheese from raw and pasteurized milk, respectively (P<0.05). There was no interaction (P>0.05) between treatment and type of cheese (pasteurized or unpasteurized) for any of the identified fatty acids. The levels of capric, lauric, myristic and palmitic acids decreased linearly (P<0.05) with increasing participation of PP in supplement concentrate. On the other hand, arachidic, lignoceric, palmitoleic and elaidic acids increased linearly (P<0.05) with the increased levels of peanut pie in the supplement concentrate. The other fatty acids showed no difference compared to the treatments studied (P>0.05). In general, cheese samples showed good acceptance, averaging between 4 (unspecified) and 5 (liked). Thus, PP may be recommended to compose the supplement concentrate in lactating cows by up to 100% replacement of SB.